THE EFFECT OF NOBLE MORAL IMPLEMENTATION TOWARDS STUDENT LEARNING OUTCOME IN SMKN 1 PALABUHANRATU - U. Abdullah Mumin (al-Afkar, Journal For Islamic Studies, 2022)
Research and surveys conducted by the Indonesian Child Protection Commission (KPAI) released 84% of data that students in Indonesia experienced a moral decline. Student behavior such as student brawl, murder, bullying, and drugs can reduce learning outcomes. A comprehensive approach is needed to overcome them, including through the application of noble character habituation. The purpose of the study was to analyze the effect of the habit of noble morals on student learning outcomes at SMK 1 Palabuhanratu. This research uses descriptive quantitative research methods with Proportionate Stratified Random Sampling. Data collection techniques with observations and questionnaires and analyzed using multiple regression. The results of this study, "Very High" (86.27%), simultaneously have a significant effect on learning outcomes with a correlation of "Strong Enough," partially the noble character of students on parents/teachers/others and their environment significantly influence the results to learn.